It is currently 21 Oct 2017, 09:14

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# Events & Promotions

###### Events & Promotions in June
Open Detailed Calendar

# Last year the price per share of stock X increased by k%,

Author Message
TAGS:

### Hide Tags

Director
Joined: 14 Sep 2005
Posts: 984

Kudos [?]: 215 [0], given: 0

Location: South Korea
Last year the price per share of stock X increased by k%, [#permalink]

### Show Tags

11 Dec 2005, 06:35
00:00

Difficulty:

(N/A)

Question Stats:

83% (00:58) correct 17% (01:23) wrong based on 21 sessions

### HideShow timer Statistics

Last year the price per share of stock X increased by k%, and the earnings per share of X increased by m%(k>m), by what percent did the ratio of the price per share to earnings per share increase?(in term of k and m)?

OPEN DISCUSSION OF THIS QUESTION IS HERE: last-year-the-price-per-share-of-stock-x-increased-by-k-89307.html
_________________

Auge um Auge, Zahn um Zahn !

Kudos [?]: 215 [0], given: 0

SVP
Joined: 05 Apr 2005
Posts: 1708

Kudos [?]: 94 [0], given: 0

### Show Tags

11 Dec 2005, 08:53
before,
price =mps = p
earning=eps=e
mps/eps ratio, before = p/e

after,
rate of increase, mps=k
rate of increase, eps=m
price =mps = p (1+k)
earning=eps=e (1+m)
mps/eps ratio, after = p(1+k)/e(1+m)
increase in the ration, = [p(1+k)/e(1+m) - (p/e)]/ (p/e) = (k-m)/(1+m)

will revise, if any error.

Kudos [?]: 94 [0], given: 0

Director
Joined: 14 Sep 2005
Posts: 984

Kudos [?]: 215 [0], given: 0

Location: South Korea

### Show Tags

12 Dec 2005, 10:26

A. k/m %

B. (k-m)%

C. [100(k-m)]/(100 + k)%

D. [100(k-m)]/(100 + m)%

E. [100(k-m)]/(100 + k + m)%
_________________

Auge um Auge, Zahn um Zahn !

Kudos [?]: 215 [0], given: 0

SVP
Joined: 05 Apr 2005
Posts: 1708

Kudos [?]: 94 [1], given: 0

### Show Tags

12 Dec 2005, 18:33
1
KUDOS
HIMALAYA wrote:
before,
price =mps = p
earning=eps=e
mps/eps ratio, before = p/e

after,
rate of increase, mps=k
rate of increase, eps=m
price =mps = p (1+k)
earning=eps=e (1+m)
mps/eps ratio, after = p(1+k)/e(1+m)
increase in the ration, = [p(1+k)/e(1+m) - (p/e)]/ (p/e) = (k-m)/(1+m)

will revise, if any error.

its D.

before,
price =mps = p
earning=eps=e
mps/eps ratio, before = p/e

after,
rate of increase, mps=k
rate of increase, eps=m
price =mps = p (100+k)%
earning=eps=e (100+m)%
mps/eps ratio, after = p(100+k)/e(100+m)%
increase in the ration, = [{p(100+k)/e(100+m) - (p/e)}/ (p/e)]100 %
= 100(k-m)/(100+m)%

Kudos [?]: 94 [1], given: 0

CEO
Joined: 20 Nov 2005
Posts: 2892

Kudos [?]: 323 [0], given: 0

Schools: Completed at SAID BUSINESS SCHOOL, OXFORD - Class of 2008

### Show Tags

14 Dec 2005, 23:11
D

Original Price: x
Original EPS = y

Ratio = x/y

Now Price = (x/100) * (1+(k/100))
Now EPS = (y/100) * (1+(m/100))

Ratio = (x/y) * [(1+(k/100)) / (1+(m/100))] = (x/y) * (100+k)/(100+m)

% Increase in ratio = [(100+k)/(100+m)] - 1 = (k-m)/(100+m)
_________________

SAID BUSINESS SCHOOL, OXFORD - MBA CLASS OF 2008

Kudos [?]: 323 [0], given: 0

Intern
Joined: 08 May 2012
Posts: 6

Kudos [?]: 6 [0], given: 1

### Show Tags

28 Jan 2013, 09:05
ps_dahiya wrote:
D

Original Price: x
Original EPS = y

Ratio = x/y

Now Price = (x/100) * (1+(k/100))
Now EPS = (y/100) * (1+(m/100))

Ratio = (x/y) * [(1+(k/100)) / (1+(m/100))] = (x/y) * (100+k)/(100+m)

% Increase in ratio = [(100+k)/(100+m)] - 1 = (k-m)/(100+m)

I dont seem to understand how you simplified (x/y) * [(1+(k/100)) / (1+(m/100))] to become (x/y) * (100+k)/(100+m)

Sorry, i know this is very basic but if one of you could just explain it to me, i would highly appreciate it.
thanks!

Kudos [?]: 6 [0], given: 1

Math Expert
Joined: 02 Sep 2009
Posts: 41892

Kudos [?]: 129113 [0], given: 12194

### Show Tags

28 Jan 2013, 09:12
iwillbeatthegmat wrote:
ps_dahiya wrote:
D

Original Price: x
Original EPS = y

Ratio = x/y

Now Price = (x/100) * (1+(k/100))
Now EPS = (y/100) * (1+(m/100))

Ratio = (x/y) * [(1+(k/100)) / (1+(m/100))] = (x/y) * (100+k)/(100+m)

% Increase in ratio = [(100+k)/(100+m)] - 1 = (k-m)/(100+m)

I dont seem to understand how you simplified (x/y) * [(1+(k/100)) / (1+(m/100))] to become (x/y) * (100+k)/(100+m)

Sorry, i know this is very basic but if one of you could just explain it to me, i would highly appreciate it.
thanks!

$$\frac{x}{y}*\frac{1+\frac{k}{100}}{1+\frac{m}{100}}=\frac{x}{y}*\frac{\frac{100+k}{100}}{\frac{100+m}{100}}=\frac{x}{y}*\frac{100+k}{100}*\frac{100}{100+m}=\frac{x}{y}*\frac{100+k}{100+m}$$.

Hope it's clear.

OPEN DISCUSSION OF THIS QUESTION IS HERE: last-year-the-price-per-share-of-stock-x-increased-by-k-89307.html
_________________

Kudos [?]: 129113 [0], given: 12194

Re: Re:   [#permalink] 28 Jan 2013, 09:12
Display posts from previous: Sort by